2021
DOI: 10.1002/jbm.a.37219
|View full text |Cite
|
Sign up to set email alerts
|

Mg(OH)2 nanoparticles enhance the antibacterial activities of macrophages by activating the reactive oxygen species

Abstract: Infection often causes disastrous consequences in all fields of clinical medicine, especially orthopedics. Hence, critical efforts are being made to engineer novel nanomaterials for the treatment of orthopedic infections due to the high biocompatibility and antibacterial properties they possess. The purpose of this study was to investigate the antibacterial effects of magnesium hydroxide (Mg(OH)2) nanoparticles (NPs) in vitro and determine their possible mechanisms of action. In this study, Escherichia coli wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 49 publications
1
4
0
1
Order By: Relevance
“…[39] It has also been implicated in pathophysiological processes induced by Mg-based biomaterials. [40] Our results validated that the PI3K/Akt signaling pathway plays a role in Mg-induced neurite outgrowth, as axonal growth density and length were significantly inhibited by the PI3K/Akt inhibitor LY294002. In addition to assessing transcriptional regulation in nerve regeneration, we evaluated the expression levels of axon guidance molecules and neurotrophic factors secreted nerve regeneration.…”
Section: Discussionsupporting
confidence: 78%
“…[39] It has also been implicated in pathophysiological processes induced by Mg-based biomaterials. [40] Our results validated that the PI3K/Akt signaling pathway plays a role in Mg-induced neurite outgrowth, as axonal growth density and length were significantly inhibited by the PI3K/Akt inhibitor LY294002. In addition to assessing transcriptional regulation in nerve regeneration, we evaluated the expression levels of axon guidance molecules and neurotrophic factors secreted nerve regeneration.…”
Section: Discussionsupporting
confidence: 78%
“…The ionic radius of Mg ++ is 72 pm [ 137 ]. The mode of action involves activating ROS [ 141 ]. They are generally considered safe, although high concentrations can cause gastrointestinal complications.…”
Section: Antimicrobial Polymersmentioning
confidence: 99%
“…Bernut et al recently found reduced ROS production by macrophages could inhibit their ability to control bacteria and subsequently lead to their death (Bernut et al, 2019). In contrast, Mg (OH) 2 nanoparticles have been implicated in enhanced antibacterial activities of macrophages by activating the reactive oxygen species (Zhu et al, 2021). Therefore, a strategy to enhance ROS generation of macrophages and promote immunoregulatory response is a potential therapy to combat bacterial pathogens and control infections.…”
Section: Impact Of Auncs On the Phagocytic Ability Of Macrophagesmentioning
confidence: 99%